Complementary and alternative medicine: Interaction and communication between midwives and women. Issue 2 (June 2015) - Hall, Helen G.; Griffiths, Debra; McKenna, Lisa G.
Abstract Background Many pregnant women use complementary and alternative medicine. Although midwives are often supportive, how they communicate with women about the safe use of these therapies has received limited research attention. Aim The aim of this study was to explore how midwives interact with women regarding use of complementary and alternative medicine during pregnancy. Methods We utilised grounded theory methodology to collect and analyse data. Twenty-five midwives who worked in metropolitan hospitals situated in Melbourne, Australia, participated in the study. Data were collected from semi structured interviews and non-participant observations, over an 18-month period. Findings How midwives communicate about complementary and alternative medicine is closely associated with the meaning they construct around the woman's role in decisionmaking. Most aim to work in a manner consistent with the midwifery partnership model and share the responsibility for decisions regarding complementary and alternative medicine. However, although various therapies were commonly discussed, usually the pregnant woman initiated the dialogue. A number of contextual conditions such as the biomedical discourse, lack of knowledge, language barriers and workplace constraints, limited communication in some situations. Conclusion Midwives often interact with women interested in using CAM. Most value the woman's autonomy and aim to work in partnership. However, various contextual conditions restrain overt CAM communication in clinical practice.